Knots and borromean rings, rep-tiles, and eight queens : Martin Gardner's unexpected hanging - Gardner, Martin (The new Martin Gardner mathematical library, 2014)
"The hangman's paradox, cat's cradle, gambling, peg solitaire, pi and e - all these and more are back in Martin Gardner's inimitable style, with updates on new developments and discoveries. Read about how knots and molecules are related; take a trip into the fourth dimension; try out new dissections of stars, crosses, and polygons; and challenge yourself with new twists on classic games"--